1958
DOI: 10.1021/ie50588a039
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Decomposition of Hydrogen Peroxide and Uranyl Peroxide

Abstract: These decomposition rates will be of prime interest in operating the newer homogeneous reactors he fuel for homogeneous research reactors is enriched uranium present as uranyl sulfate in an ordinary (light)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1971
1971
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Early work focused on the formation of uranyl peroxides in engineered systems (e.g. light‐water reactors), but a more thorough understanding of these phases began with the characterization of the naturally occurring peroxide‐containing minerals studtite and metastudtite . Uranium ore deposits emit α‐radiation, which can radiolytically split water molecules into hydroxyl and superoxide radicals and ultimately form solid uranyl peroxide phases .…”
Section: Figurementioning
confidence: 99%
“…Early work focused on the formation of uranyl peroxides in engineered systems (e.g. light‐water reactors), but a more thorough understanding of these phases began with the characterization of the naturally occurring peroxide‐containing minerals studtite and metastudtite . Uranium ore deposits emit α‐radiation, which can radiolytically split water molecules into hydroxyl and superoxide radicals and ultimately form solid uranyl peroxide phases .…”
Section: Figurementioning
confidence: 99%
“…The temperature dependence of the solubility product of uranyl peroxide can also be extracted from the titration test data (Figure 5, right). Based on the measured rate of thermal decomposition of H 2 O 2 in uranyl sulfate (Figure 6, adapted from Silverman et al [3]), we can account for the amount of peroxide lost during elevated temperature titrations. This allowed us to quantify how the K sp of the metastudtite precipitate changes from 25 o C to 60 o C (Figure 5).…”
Section: Figure 5 Results From Titration Tests (Data Points) and Thermentioning
confidence: 99%
“…In the fissioning of an LEU solution as uranyl sulfate for production of Mo-99 to be used in medical applications, peroxide formation from radiolysis can lead to precipitation of uranyl peroxide [1]. Work on aqueous homogenous reactors with uranyl sulfate fuel in the 1950s showed that the reactor power is limited by the concentration of peroxide produced by fission fragments in solution [2,3]. The concentration of radiolytic peroxide increases as the power density increases until the fuel solution becomes saturated with respect to uranyl peroxide.…”
Section: Introductionmentioning
confidence: 99%
“…
Current synthetic pathwaysf or uranyl peroxide materials introduce high initial concentrations of aqueous H 2 O 2 that decline over time.Alternatively,insitu generation of organic peroxide would maintain constant concentrations of peroxideo ver prolonged periods of time and open new pathwayst on ovel uranyl peroxide compounds.H erein, we demonstrate this concept through the synthesis of ananotubelike uranyl peroxide phosphate (NUPP), Na 12 [(UO 2 )(m-O 2 )-(HPO 4 )] 6 (H 2 O) 40 ,making use of the inhibited autoxidation of benzaldehyde in benzyl alcohol solutions in the presence of phosphonate ligands.The unique feature of NUPP is the bent dihedral angle U-(m-O 2 )-U (123.98 8 AE 0.48 8 to 124.68 8 AE 0.58 8), which allows hexameric uranyl peroxide macrocycles to adopt the nanotubular topology and prevents the formation of nanocapsules.R aman spectroscopyo ft he solution phase confirms our mechanistic understanding of the reaction pathway and confirms that consistent levels of peroxidea re generated in situ over an extended period of time.Uranium peroxide solids were first synthesized from aqueous solutions in 1876 and additional literature precedent supports their prevalence in diverse chemical environments. [1] Early work focused on the formation of uranyl peroxides in engineered systems (e.g.l ight-water reactors), [2,3] but am ore thorough understanding of these phases began with the characterization of the naturally occurring peroxide-containing minerals studtite and metastudtite. [4] Uranium ore deposits emit a-radiation, which can radiolytically split water molecules into hydroxyl and superoxide radicals and ultimately form solid uranyl peroxide phases.
…”
mentioning
confidence: 99%
“…Uranium peroxide solids were first synthesized from aqueous solutions in 1876 and additional literature precedent supports their prevalence in diverse chemical environments. [1] Early work focused on the formation of uranyl peroxides in engineered systems (e.g.l ight-water reactors), [2,3] but am ore thorough understanding of these phases began with the characterization of the naturally occurring peroxide-containing minerals studtite and metastudtite. [4] Uranium ore deposits emit a-radiation, which can radiolytically split water molecules into hydroxyl and superoxide radicals and ultimately form solid uranyl peroxide phases.…”
mentioning
confidence: 99%